RANCANG BANGUN APLIKASI INVENTORY METODE FIFO DAN LAPORAN STOK BARANG PADA KPRI “MANFAAT” LEMBAGA PENJAMIN MUTU PENDIDIKAN (LPMP) JAWA TENGAH MENGGUNAKAN MICROSOFT VISUAL BASIC.NET - Alfian Nurdiansyah; Afiat Sadida (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
The purpose of this paper is to build an inventory information systemapplication program using the FIFO method and the Stock Report using MicrosoftVisual Basic. NET to reduce errors in calculations and inventory recording errorswhose operations can be easily understood by users. Data collection methods used are interview methods, observation and literature study. The writing method used in this research is the description method which explains the general profile of the Central Java Education Quality Assurance Agency (LPMP) KPRI and the exposition method to explain the results of the system design being implemented. It is hoped that the FIFO method of inventory system design and inventory reports will minimize the problems encountered so that it can produce reports and display accurate data according to actual conditions.For the preparation of the FIFO method of inventory information system software and inventory reports, there are several stages: system analysis, process analysis, conceptual design, detailed design, implementation and conversion. Reports generated include the FIFO method inventory of goods reports, goods inward reports, goods outgoing reports and goods returns reports.